Contributions of Jets in Net Charge Fluctuations from the Beam Energy Scan at RHIC and LHC - Bushra Ali; Shaista Khan; Shakeel Ahmad (Advances in High Energy Physics)
Dynamical net charge fluctuations have been studied in ultrarelativistic heavy-ion collisions from the beam energy scan at RHIC and LHC energies by carrying out the hadronic model simulation. Monte Carlo model, HIJING, is used to generate events in two different modes, HIJING-default with jet quenching switched off and jet/minijet production switched off. A popular variable, ν[+-,dyn], is used to study the net charge fluctuations in different centrality bins and the findings are compared with the available experimental values reported earlier. Although the broad features of net charge fluctuations are reproduced by the HIJING, the model predicts the larger magnitude of fluctuations as compared to the one observed in experiments. The role of jets/minijets production in reducing the net charge fluctuations is, however, distinctly visible from the analysis of the two types of HIJING events. Furthermore, dNch/dη and 1/N scaling is partially exhibited, which is due to the fact that, in HIJING, nucleus-nucleus collisions are treated as multiple independent nucleon-nucleon collisions.